A comparative effectiveness study of the breaking the cycle and Maxxine Wright intervention programs for substance-involved mothers and their children: study protocol - Racine, Nicole; Barriault, Sophie; Motz, Mary; Leslie, Margaret; Poole, Nancy; Premji, Shainur; Andrews, Naomi C. Z.; Penaloza, Denise; Pepler, Debra (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background Children of substance-involved mothers are at especially high risk for exposure to adverse childhood experiences (ACEs) and poor mental health and development. Early interventions that support mothers, children, and the mother-child relationship have the greatest potential to reduce exposure to early adversity and the mental health problems associated with these exposures. Currently, there is a lack of evidence from the real-world setting demonstrating effectiveness and return on investment for intervention programs that focus on the mother-child relationship in children of substance-involved mothers. Methods One hundred substance-involved pregnant and/or parenting women with children between the ages of 0–6 years old will be recruited through the Breaking the Cycle and Maxxine Wright intervention programs, in Toronto, Ontario, Canada and Surrey, British Columbia, Canada, respectively. Children’s socioemotional development and exposure to risk and protective factors, mothers’ mental health and history of ACEs, and mother-child relationship quality will be assessed in both intervention programs. Assessments will occur at three time points: pre-intervention, 12-, and 24-months after engagement in the intervention program. Discussion There is a pressing need to identify interventions that promote the mental health of infants and young children exposed to early adversity. Bringing together an inter-disciplinary research team and community partners, this study aligns with national strategies to establish strong evidence for infant mental health interventions that reduce child exposure to ACEs and support the mother-child relationship. This study was registered with clinicaltrials.gov (NCT05768815) on March 14, 2023.